Heat Capacity and Thermodynamic Functions of Cerium Tellurites in the Range of 298.15–673 K - Rustembekov, K.T.; Dyusekeeva, A.T.; Fomin, V.N.; Makhatova, N.A. (RUSSIAN JOURNAL OF PHYSICAL CHEMISTRY A, 2015)
The isobaric heat capacity of cerium tellurites is studied in the range of 298.15–673 K and used as a basis for deriving dependences ~ f(T) and determining their thermodynamic functions. Dependences ~ f(T) are found to have abnormally sharp λ like peaks, due probably to second order phase transitions.
Keywords: calorimetry; heat capacity; calcium–cerium tellurites; strontium–cerium tellurites; second order phase transitions; thermodynamic functions